Pengaruh Modal Sendiri, Modal Pinjaman Dan Lama Usaha Terhadap Pendapatan Pedagang Kecil Pengrajin Keripik Di Kawasan Sentra Industri Keripik (Gang Pu) Jalan Za. Pagar Alam Bandar Lampung - Tri Wulan Mayasari; Indah Lia Puspita; Hardini Ariningrum (Universitas Malahayati, 2015)
Abstract. Micro, small and medium scale businesses. have significant role for Indonesia’s economy.These may enrich job opportunity, income and wealth increase, economy development and nationalstability. Micro, small and medium scale businesses, development met some obstacles. The commondifficulties included limited capital and its access, marketing, distribution and material sourcesproblems as well as qualified human surces. This study was to identify the effect of owner equity, loancapital and business age towards income on small traders of banana chips at Gang PU Home IndustryDistrict on Pagar Alam Street of Bandar Lampung. The objects were small traders of banana chips at 4Km long Pagar Alam Street of Bandar Lampung. Analysis instruments were classical assumption,double linear regression test,T test partial, Stimulant Test with F Test generated on SPSS version 16.T Test found that. partially. there were effects among owner's equity and loan capital towards income.Meanwhile, business age did not affect income. F Test revealed that owner’s equity. loan capital andbusiness age, simultaneously, influenced income.